Prosedur Penyelidikan terhadap Tindak Pidana yang Dilakukan oleh Anggota TNI AD (Studi di Subdenpom V/4-3 Pamekasan) - Maskun Maskun; Setiyono Setiyono (MLJ Merdeka Law Journal, 2022)
This study aims to examine and analyze the Investigative Procedures Against Criminal Acts Performed by Indonesian Army Soldiers in Subdenpom V/4-3 Pamekasan and the obstacles in the Investigation Procedures Against Crimes Performed by Indonesian Army Soldiers in Subdenpom V/4-3 Pamekasan. Using the interactive analysis model or Interactive Model of Analysis, it was found that the procedure for investigating crimes committed by TNI AD Soldiers at Subdenpom V/4-3 Pamekasan was in accordance with what was mandated in Chapter IV Part One Articles 69 to 98 of Law Number 31 of 1997 regarding military justice which contains an investigation starting from the existence of a police report, requirements for a police report, summons to suspects and witnesses, examination of suspects and sanctions, arrest and detention and carrying out of investigations. Obstacles in Investigating Procedures for Crimes Performed by Indonesian Army Soldiers are the lack of witness participation in providing information in the investigation process, there are still some investigators whose education level is still low, the limited number of personnel and the lack of budget for investigations.DOI: https://doi.org/10.26905/mlj.v3i1.9432